2019
DOI: 10.1002/ajmg.a.61264
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric osteolytic syndromes represent a phenotypic spectrum defined by defective collagen remodeling

Abstract: Frank-Ter Haar syndrome (FTHS), Winchester syndrome (WS), and multicentric osteolysis, nodulosis, and arthropathy (MONA) are ultra-rare multisystem disorders characterized by craniofacial malformations, reduced bone density, skeletal and cardiac anomalies, and dermal fibrosis. These autosomal recessive syndromes are caused by homozygous mutation or deletion of respectively SH3PXD2B (SH3 and PX Domains 2B), MMP14 (matrix metalloproteinase 14), or MMP2. Here, we give an overview of the clinical features of 63 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 94 publications
(301 reference statements)
3
27
0
Order By: Relevance
“…For instance, over half of the members of the MMP family are involved in promoting bone growth and development under normal physiological conditions, 6 and mutations in the human MMP2 and MMP14 genes have been linked to rare skeletal diseases characterized by loss of bone tissue and short stature. 7 MMPs are produced by a wide variety of cell types (eg, stromal fibroblasts, macrophages, and endothelial and epithelial cells) and are expressed as inactive zymogens (proenzymes) containing a propeptide domain that must be removed for protease activity. 2,4,8 In vertebrates, there are at least 28 different MMPs, and at least 23 of them are expressed in humans.…”
Section: Overview Of the Role Of Mmps In Health And Diseasementioning
confidence: 99%
“…For instance, over half of the members of the MMP family are involved in promoting bone growth and development under normal physiological conditions, 6 and mutations in the human MMP2 and MMP14 genes have been linked to rare skeletal diseases characterized by loss of bone tissue and short stature. 7 MMPs are produced by a wide variety of cell types (eg, stromal fibroblasts, macrophages, and endothelial and epithelial cells) and are expressed as inactive zymogens (proenzymes) containing a propeptide domain that must be removed for protease activity. 2,4,8 In vertebrates, there are at least 28 different MMPs, and at least 23 of them are expressed in humans.…”
Section: Overview Of the Role Of Mmps In Health And Diseasementioning
confidence: 99%
“…This enzyme can be activated extracellularly and intracellularly and is involved in multiple pathways. Mutations in this gene are associated with the Winchester syndrome [34]. Recent studies have indicated that MMP2 is highly expressed in many tumors, and its increase promotes proliferation and metastasis, and reduces tumor cell apoptosis [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In general, most children with MMP2 mutations are apparently healthy at birth, but signs of skeletal deformities begin from six months to eleven years old. Thereafter, features of arthropathy gradually appear, including joint pain, joint contracture and swelling of distal extremities, and other symptoms then progressively develop, such as coarse facies and gum hypertrophy (36). Vanatka et al (37) reported a case of MONA with long-term follow-up, in which the pathological changes of the bones over a 23-year period were striking and the pattern of bone loss was progressive and periarticular.…”
Section: Mmp2 In Hereditary Skeletal Dysplasiamentioning
confidence: 99%